ANALISIS TINGKAT UTILITAS SISTEM ANTRIAN PADA PT POS INDONESIA KOTA PAREPARE - Ramadhana, Nur Asmi (DECISION : Jurnal Ekonomi dan Bisnis, 2021)
This study aims to analyze the utility level of the service queue system at PT. Pos Indonesia Kota Parepare. This research supports the analysis of the utility level of the service queue system at PT. Pos Indonesia, the city of Parepare. From the analysis results obtained queuing system at PT. Pos Indonesia, Kota Parepare M / M / S double-track queue model. The results of calculations with the M / M / S queuing model at PT. Pos Indonesia, Kota Parepare implements queuing discipline, namely First Come First Server (FCFS). Patterns of the arrival of customers, distribution of passion from the results of calculations with the dual-line queuing system model (M / M / S), it is known that PO is 3.90%, while the post for 50% of the time is free of 50% (free service hours). Ls 5,423 people or five people. Lq 3,423 people or three people, Ws 0.112 hours or 6.7 minutes, while Wq 0.071 hours or 4.27 minutes.